Whose German Literature? GDR-Literature, German Literature and the Question of National Identity - Patricia Herminghouse (GDR Bulletin, 1990)
This paper grew out of concluding comments made at the Washington conference; in its present form it is a slightly revised version of a presentation at the MLA annual meeting a month later.